Research On the Motivation of Rural Tourism Based on Grounded Theory in The Post-Covid-19 Era - Wei Wang; Carlos Orús Sanclemente; María Vicoria Sanagustín Fons (Communications of International Proceedings, 2021)
At the beginning of 2020, the Covid-19 pandemic swept the world, infecting tens of millions of people and putting many countries under a state of emergency. As a fragile and sensitive industry, the tourism industry has suffered a major impact during the pandemic and was once in a state of "shutdown”. During the pandemic, consumers were unable to travel across regions due to government restrictions on footsteps, and the villages around their places of residence became the first choice for tourism. This research analyses the psychological motivation of rural tourism with grounded theory. The study found that individual travel motivation can be divided into experience motivation, relationship promotion motivation, self-development motivation and self-realization motivation during the Covid-19.
Keywords: Grounded Theory; Post-Covid-19 Era; Rural Tourism; Motivation